ANALISIS KARAKTERISTIK CURAH HUJAN PENYEBAB BANJIR BERDURASI PANJANG (STUDI KASUS: BANJIR TAHUN 2019 DI BALEENDAH, JAWA BARAT) - Simanjuntak, Yogi Sahat Maruli; Suwarman, Rusmawan; Edi, Riawan (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
In 2019, Baleendah experienced flooding with a duration of ± 30 days, this can be seen from the water level which is above the critical point from February 9th – March 12th, 2019, which identified the occurrence of flooding. Based on the spatio-temporal analysis of rainfall in the upstream Citarum watershed that drains to Baleendah, there were differences in the timing of rainfall between northern, southern, and eastern regions, and a semi-diurnal pattern. This study aims to look at the rainfall pattern that causes long-duration flooding in Baleendah. Based on that point, we conducted hydrological simulations using the Hydrologic Engineering Center’s Hydrologic Model System (HEC-HMS) with the assumption that the volume of rainfall is constant. The rainfall scenarios used were 1) a diurnal scenario where there is a difference in the timing of rainfall between the north, south, and east regions, 2) rainfall scenarios with diurnal and semidiurnal variations, and 3) the semidiurnal scenario is getting closer (the timing between rainfall in the morning and in the night is getting closer) in the north, south, and east regions. The results of this study show that floods are longer in duration and peak discharge is higher when a diurnal pattern occurs. Rainfall is initiated in the eastern and southern regions and a lag in timing rainfall occurred in the northern region.Keywords: Baleendah, Long duration flood, rainfall time difference, variation of diurnal and semidiurnal, and short semidiurnal